Hubungan antara Kondisi Sanitasi Lingkungan Rumah dengan Kecacingan pada Murid Sekolah Dasar Bandarharjo 02-04 Kotamadia Semarang - Dharminto, Dharminto (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2002)
In the same manner as the other developing countries, Indonesia also remains face the difficulties against the high prevalence rate of infectious diseases, particularly, ones that related with bad environmental condition. one of them, which is usually occurred in elementary school children and have a negative effect on thei growth and development, is soil transmitted helminthiasis, an infection of intestinal worm transmitted through soil or known as helminthic disease. three kinds of them are Ascarislumbricoides, whipworm (Trichuris trichiura), and hookworm (Necator americanus and Ancylostoma duodenale). Is there any relationship between house sanitation and the occurrence of helminthic diseaseon students of Bandarharjo 02-04 Elementary School ?This research is a cross-sectional survey. Population used in this research is 4th and 5th grade students of Bandarharjo 02-04 Elementary School in Tanjung Mas District. The children’s Stool werw examined by the Kato-Katz method.The Study showed that there was no relationship between house sanitation with the occurrence of helminthic diseaseKeywords: Environmental Health Sanitation, soil transmitted helminths, pupils.